THE EFFECT OF LOW LEVEL OF OZONE ON GROWTH AND DEVELOPMENT OF RHIZOPUS SP. IN VITRO - Hartati Oktarina; Ian Singleton; Sanjay Anthony-Babu (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
Postharvest diseases caused by microbial pathogens account for a great loss every year. Fungicides have been used for decade to control spoilage in conventional agriculture. It is generally known that long term use of chemical would harm the environment and bring resistance to organisms. Increasing public concern over the use of conventional fungicide due to health issues has prompted investigations to find alternative environmentally friendly control agent that might be used to suppress diseases development in storage.Ozone has been considered by researchers as an effective alternative to the use of traditional pesticides in food preservation because it leaves no residue on fresh produce so that safer to consumed.This work determined the effect of low level ozone exposure (180 ppb) on colony development and spores production of Rhizopus oryzae, R. stolonifer and R. microsporus var.chinensis in vitro. Two types of inocula were used, mycelial and spore, as both are responsible for spread of spoilage when stored with uncontaminated food. The tested fungi were stored in an ozone chamber at 7-8 oC for 14 days. Colony development was studied by measuring the colony diameter while spores production by time fungi was assed on the 14th day of the incubation period. Ozone exposure at 180 ppb has varied result on colony development and spore production on each species examined.Overall the work suggests that continuous low level of ozone exposure at 180 ppb for 14 days has different effect on different species depend on the ability each microorganism to counteract with ozone exposure.